Effects of piglet enrichment on sow skin lesions and behavior before and after tail docking and castration - Bučková, Katarína; Newgard, Alexa M.; Tomko, Lainey J.; Arnold, Kailey M.; Johnson, Anna K. (Frontiers in Ethology, 2025)
Commercially housed pigs face multiple welfare challenges, such as painful husbandry procedures or a lack of environmental enrichment. We evaluated sow behavior in response to piglets experiencing tail docking and castration. Our second objective was to assess the effects of environmental enrichment for piglets on sow teats and skin lesions. Shortly before farrowing, three commercially available piglet toys and a jute bag were installed in 12 farrowing stalls. Eleven farrowing stalls were not equipped with any enrichment. Sows were provided ad libitum access to water, and they were hand-fed to appetite two times daily (7 a.m. and 3 p.m.) in 0.90-kg increments. All piglets were tail-docked, and males were surgically castrated at 7 days of age. Sow behavior was recorded by cameras mounted on the ceiling from 5 to 7 p.m. a day before processing and on the processing day. The videos were watched continuously by two observers in BORIS. The differences in pre- and post-processing sow behaviors were tested using a paired t-test. All sows were inspected for teat inflammation, scabs, wounds, splits, and missing teat tips before farrowing and at the end of lactation. Data were analyzed using the SAS GENMOD procedure with a Poisson distribution. Sows were inspected for skin lesions using the Welfare Quality® Assessment protocol at 6, 14, and 19 days post-farrowing and analyzed using the SAS GLIMMIX procedure with multinomial distribution. All sows decreased feeding (p = 0.001) and standing (p = 0.045) after piglets were tail-docked and/or castrated. Sows whose piglets did not have enrichments also decreased nosing stall structure (p = 0.01) and posture change (p = 0.04). No other sow behaviors changed in relation to piglet processing (p > 0.05). Similarly, enrichments for piglets had no significant effect on sow teat or skin lesions. In conclusion, this is the first study reporting that tail docking and surgical castration may have negative effects on sow behavior. Additionally, these findings contribute to the growing body of literature that, from an animal welfare perspective, tail docking and surgical castration should be refined or avoided.